Seroprevalence and Geographical Distribution of Rift Valley Fever in Livestock in Sudan - Mohammed E. A. Mansour; Ayman Ahmed; Selma Kamal; Tamador M.A. Elhassan; Atif Elamin Abdelgadir (Journal of Applied Veterinary Science And Technology, 2024)
Background: Rift Valley Fever (RVF) is zoonotic and Transboundary Animal Disease (TAD) that has public health and trade implications for livestock and livestock products. It occurs following heavy rains and is characterized by miscarriages in small ruminants, such as sheep and goats, and illness in humans. The mosquito is the main vector for the disease. It can be transmitted by direct contact with tissues, aerosol, and blood of the infected individual and by ingestion of raw and/or uncooked milk. Purpose: This study aims to estimate the seroprevalence of RVF in Sudan and to determine the geographical distribution of RVF to understand the pattern of its occurrence in Sudan. Methods: This study was conducted in Central Sudan. This study was a retrospective study in which the data were collected mainly from archives and records of the laboratory and were used to estimate the seropositivity. The target population in this study was concentrated on livestock, especially ruminants. Results: In this study, the overall seroprevalence of RVF was estimated to be 16%. The highest seroprevalence was recorded at 66% in cattle in River Nile (95% CI [60.37171, 73.44393]), whereas the lowest seroprevalence was recorded at 0.8% in cattle in Blue Nile (95% CI [0.73293, 0.96704]). Conclusion: This study concluded that herd immunity is a significant factor in understanding the epidemiology of RVF in Sudan. In addition, the retrospective data provided a roadmap for managing and controlling transboundary diseases that have had an impact on human health.